La producción legislativa y el control político ¿hacia donde se inclina la balanza del equilibrio del poder político en Colombia? (2016)
The work presented in itself a reflection on legislative output, an activity carried out by the legislature and special meetings by the executive and the core of modern constitutional law, that is, the idea of political control to guarantee compliance with the principle of separation and coordination of state powers as a condition for the existence of a genuine constitutional rule. The research process develops an analysis of the legislative process from 1991 to 2010 in the presidencies of Cesar Gaviria, Ernesto Samper, Pastrana and Alvaro Uribe, in Colombia determining who has greater scope in producing the Government or Laws the Congress, and gives explanations about this phenomenon, studies and cases of Political Control in Colombia during the same period 1991-2010: Points of Debates Censorship and Political Control in order to establish and operate the control Political in Colombia.